Academic Integrity: Preventing Students’ Plagiarism with TURNITIN - Ismail Ismail; Umiyati Jabri (Universitas Muhammadiyah Enrekang, 2023)
The problem of plagiarism in writing scientific articles is intellectual dishonesty and received a lot of attention during this research, and relatively few students understand about plagiarism. A total of 16 respondents from final year students of the English education department involved in this research. The single group pretest-posttest comparative method was used to assess an action to determine the performance gap between the two time periods, before and after the intervention. Student papers were first submitted to measure their level of plagiarism without their knowledge. The results showed that Muhammadiyah Enrekang students practiced plagiarism on average 50.88%. Subsequently, the students were introduced by Turnitin's plagiarism detecting software and advised to examine their writing using software. The learning model intervention is then carried out with development training. The results showed that the average level of plagiarism among students decreased by 18.81%. In terms of students' perceptions of using Turnitin as a standard way of submitting their final assignments and to get feedback, the overall student reaction to the system used was positive. To avoid plagiarism, a more systematic approach should be taken by the University towards the problem of academic dishonesty, and in particular by students for the specific reasons why they practice plagiarism.